ROI for a customer relationship management initiative at GST - Jeffery, Mark, 1965- (SAGE Business Cases., 2006)
This case "ROI for a Customer Relationship Management Initiative at GST" addresses key issues related to large revenue-generation IT projects. The key topics covered are: measurement of return on investment and project payback period, the decision of what time horizon and hurdle rate to use, the importance of business assumptions in the model, and additional management issues beyond the basic analysis. The case debrief focuses on the strategy of a firm in a high customer-churn environment and the ability of analytical customer relationship management to provide strategic advantage.